Review of hematuria case-based perspective with emphasis on vascular cause: Nutcracker syndrome - İleri, Sara (The European Research Journal, 2025)
Hematuria, the presence of erythrocytes in urine, is classified into two main types: macroscopic, visible to the naked eye, and microscopic hematuria not visible without a microscope. A careful medical history is the best guide for evaluation. Hematuria accompanied by proteinuria or hypertension is particularly significant in differential diagnosis. Treatment options range from regular follow-up to nephrectomy; thus, an accurate and early diagnosis is essential for managing patients with hematuria. A 52-year-old Caucasian white female presented with painless hematuria. Cystoscopy was performed following the initial ultrasound evaluation. Urine cytology and pathological findings were benign. Renal function test results were within normal limits, and there was no proteinuria. Urinary sediment analysis revealed 10–15 isomorphic erythrocytes per high-power field. Glomerulonephritis was excluded in the diagnosis. Her medical history revealed a Whipple procedure performed three years earlier. So, Doppler ultrasound was performed to assess the possibility of renal vein compression. Doppler imaging revealed that the diameter of the left renal vein was 9.5 mm before the superior mesenteric artery and 1.8 mm after it, findings consistent with Nutcracker Syndrome. As her renal function was normal and she was normotensive, clinical follow-up was recommended at six-month intervals. Nutcracker Syndrome is a rare vascular compression disorder that typically involves entrapment of the left renal vein between the aorta and superior mesenteric artery. Given the risk of unnecessary interventions, this rare condition should be considered and excluded in the differential diagnosis of hematuria.